Enhanced Transdermal Delivery of Bisoprolol Hemifumarate via Combined Effect of Iontophoresis and Chemical Enhancers: Ex Vivo Permeation/In Vivo Pharmacokinetic Studies - Mahmoud H. Teaima; Mohamed Azmi Ahmed Mohamed; Randa Tag Abd El Rehem; Saadia A. Tayel; Mohamed A. El-Nabarawi; Shahinaze A. Fouad (MDPI AG, 2021)
Bisoprolol hemifumarate (BH) is an antihypertensive drug that is used as first-line treatment for chronic hypertension and angina pectoris. Our study was performed to enhance the transdermal delivery of BH, a hydrophilic drug active with high molecular weight, through differently prepared hydrogels. The synergistic effect of permeation enhancers and iontophoresis was investigated via both ex vivo and in vivo permeation studies. Ex vivo iontophoretic permeation studies were performed by using male albino Wistar rat skin. Cellosolve® hydrogel (F7) showed a 1.5-fold increase in Q180, Jss, and FER compared to F5 (lacking permeation enhancer). BH pharmacokinetic data were studied in human volunteers, following transdermal delivery of F7, using Phoresor® Unit II iontophoresis device, compared to conventional oral tablets. F7 showed 1.9- and 2-fold higher values of Cmax and AUC0-40, respectively compared to Concor® tablets, as well as a smaller Tmax (2.00 ± 2.00 h). The relative bioavailability of F7 was found to be 201.44%, relative to Concor® tablets, demonstrating the significantly enhanced transdermal permeation of BH from the selected hydrogel by iontophoresis, in human volunteers. Finally, results showed the successful utility of permeation enhancers combined with iontophoresis in significantly enhanced transdermal permeation of BH, despite its large molecular weight and hydrophilic nature. Therefore, this strategy could be employed as a successful alternative route of administration to conventional oral tablets.